2013
DOI: 10.1007/s00134-013-3034-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sedation level on the prevalence of delirium when assessed with CAM-ICU and ICDSC

Abstract: Sedation per se can result in positive items of both CAM-ICU and ICDSC, and therefore in a diagnosis of delirium. Consequently, apparent prevalence of delirium is dependent on how a depressed level of consciousness after sedation stop is interpreted (delirium vs persisting sedation). We suggest that any reports on delirium using these assessment tools should be stratified for a sedation score during the assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 19 publications
5
58
3
1
Order By: Relevance
“…Fourth, we assessed the presence of delirium using the CAM-ICU. The performance of this assessment tool in daily practice has been re-evaluated recently [8,9], and also been discussed in sedated patients [38,39] and may not be as accurate as in the original validation studies [10,11], however, ongoing bedside education results in a better performance [40]. On the other hand, in the reevaluation studies the CAM-ICU was measured only once and compared with an expert screening, while in our multinational study the delirium diagnosis was based on all consecutive CAM-ICU screenings during a patients' complete ICU stay, increasing its sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we assessed the presence of delirium using the CAM-ICU. The performance of this assessment tool in daily practice has been re-evaluated recently [8,9], and also been discussed in sedated patients [38,39] and may not be as accurate as in the original validation studies [10,11], however, ongoing bedside education results in a better performance [40]. On the other hand, in the reevaluation studies the CAM-ICU was measured only once and compared with an expert screening, while in our multinational study the delirium diagnosis was based on all consecutive CAM-ICU screenings during a patients' complete ICU stay, increasing its sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were then assessed daily by a trained physician for delirium using the standardized diagnostic tool -The Confusion Assessment Method for the ICU (CAM-ICU) (ref. [34][35][36] ). The assessment was done regularly between 8 and 10 a.m., and the CAM-ICU sheet was filled in.…”
Section: Patientsmentioning
confidence: 99%
“…The different subtypes of delirium are however difficult to classify in the ICU because of confounding effects of sedation. Recent investigations have shown that the diagnosis of delirium is influenced by sedation regimes with overlap between sedation, residual sedation, and hypoactive delirium [10,23,25,26]. Another explanation for the low frequency of hyperactive delirium could be that, for example, due to ICU-acquired weakness or the use of sedatives, possible hyperactive delirious patients are less likely to score a RASS above 0.…”
Section: Discussionmentioning
confidence: 96%
“…This is important, as classifications per day cannot be based directly on results from routine CAM-ICU or ICDSC screening alone [8,19,23,24] because of low sensitivity of routine CAM-ICU screening as well as the fluctuating nature of delirium during the day. In addition, we have provided frequency measures of delirium and delirium duration, which can be used to design future studies on delirium in the ICU.…”
Section: Discussionmentioning
confidence: 99%